-2-z=z-6

Simple and best practice solution for -2-z=z-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-z=z-6 equation:



-2-z=z-6
We move all terms to the left:
-2-z-(z-6)=0
We add all the numbers together, and all the variables
-1z-(z-6)-2=0
We get rid of parentheses
-1z-z+6-2=0
We add all the numbers together, and all the variables
-2z+4=0
We move all terms containing z to the left, all other terms to the right
-2z=-4
z=-4/-2
z=+2

See similar equations:

| -6(3x-9)=18 | | z2=4z | | 18x-41=4x+35 | | 1+2p=2p+1 | | 5x-18+6x=-7 | | -5(6+9d)=-34 | | (5x+1)+49=90 | | 9x+15=3x | | -4(2x-6)=28 | | (5x1)49=90 | | -3-9(1+8b)=25 | | x^2-6x+18=3x^2-x+6 | | (x+1)+49=90 | | 2x+2=-5x+9 | | 47=-10+x | | x+x*2=141 | | (4x+5)+(5x+4)=90 | | -13x-47=-14x+3-9x | | 2x*2=141 | | -4x+18=-2x | | (x+17)+55=90 | | -3(2x+4=-9 | | -8v+4=-20 | | -7x-4+3=-34 | | 7⋅m=56 | | -15x-25=2x-22-21 | | -3x+76=-9x-8 | | (2+5x)+(2x+10)=180 | | (2x+6)=220 | | 3k-1=7k2 | | 12m-4-4m-9=4m+5-2 | | |n|+2=5 |

Equations solver categories